2010
DOI: 10.2507/ijsimm09(3)2.158
|View full text |Cite
|
Sign up to set email alerts
|

Aspect of selective rerouting in multicriteria scheduling of flexible manufacturing

Abstract: In this paper, a Multi-Criteria Scheduling Algorithm (MCSA) based on swapping of dispatching rules and Selective Rerouting (SR) approach based on lateral entry of critical jobs in the queue of alternate machine is used. Further, the effect of simultaneous application of MCSA and SR has been investigated. The system performance has been evaluated using mean flow time, maximum flow time, mean tardiness and maximum tardiness as the performance measures. Simulation studies using ProModel ® simulation software were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The authors have reported selective rerouting approach based on lateral entry of critical jobs in queue of the alternative machine in their previous work [22]. In this paper this approach has been employed in a flexible job shop and the inferences drawn from the research are discussed in the subsequent sections.…”
Section: Selective Rerouting Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have reported selective rerouting approach based on lateral entry of critical jobs in queue of the alternative machine in their previous work [22]. In this paper this approach has been employed in a flexible job shop and the inferences drawn from the research are discussed in the subsequent sections.…”
Section: Selective Rerouting Approachmentioning
confidence: 99%
“…Hence, there is a need to develop efficient reactive policies, which can improve the performance of the priority heuristics due to the impact of shop floor disruptions. Hence, to full fill the gaps of the literature review author developed the selective rerouting algorithm in his previous work [22]. In the present work, the simulation study of the selective rerouting algorithm has been carried out in the flexible job shop environment.…”
Section: Introductionmentioning
confidence: 99%